Peran Kyai Dalam Pengaruh Moderasi Beragama di Tengah Isu Digital - Nur Fauzi, Ahmad; Nur Fadhila, Indah; Yaenuri, Ali (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This research originates from the researcher’s concern about the state of religious moderation in the digital space, despite the Ministry of Religious Affairs of the Republic of Indonesia having emphasized the discourse on religious moderation since 2019. However, the actualization of this discourse has not been fully realized, especially on social media. The research examines this shortcoming by exploring the role of